2020
DOI: 10.1088/1361-6404/ab9a0a
|View full text |Cite
|
Sign up to set email alerts
|

Small oscillations of a rigid sphere on an elastic half space: a theoretical analysis

Abstract: Harmonic motion is a significant topic in undergraduate lectures for university physics students. A typical example, presented in lectures around the globe, is the motion of a mass at the end of a spring. It should be emphasized that the harmonic motion in the aforementioned case is just an approximation for small displacements. However, the value of this example for teaching purposes is undeniable, if used properly. Its significance is connected to the adoption of an analytical way of thinking by the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Firstly, the sample that is being indented should be flat, homogeneous and isotropic and the indenter should be significantly smaller compared to the sample's dimensions (in other words the sample should behave as an elastic half space. An elastic half space is an elastic material that extends infinitely in all directions including the depth, with the surface at the top as boundary [39]). Secondly, the contact between the sample and the indenter should be adhesionless and frictionless.…”
Section: Correlating the Applied Force The Contact Radius And The Ind...mentioning
confidence: 99%
“…Firstly, the sample that is being indented should be flat, homogeneous and isotropic and the indenter should be significantly smaller compared to the sample's dimensions (in other words the sample should behave as an elastic half space. An elastic half space is an elastic material that extends infinitely in all directions including the depth, with the surface at the top as boundary [39]). Secondly, the contact between the sample and the indenter should be adhesionless and frictionless.…”
Section: Correlating the Applied Force The Contact Radius And The Ind...mentioning
confidence: 99%
“…The aforementioned motion is described by a second-order nonlinear ordinary differential equation that presents significant complexity [32]. In a previous publication, it was shown that for small displacements, the sphere's motion can be considered as harmonic [32]. However, in this paper, cases with significant displacement range will be explored.…”
Section: Introductionmentioning
confidence: 97%
“…The problem to be studied in this paper is the nonlinear oscillation of a rigid sphere on an elastic half-space. The aforementioned motion is described by a second-order nonlinear ordinary differential equation that presents significant complexity [32]. In a previous publication, it was shown that for small displacements, the sphere's motion can be considered as harmonic [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhupanska and Ulikto [26] used a similar approach to solve the contact of a rigid cylinder indenting an elastic half-space, both for non-slipping and slipping conditions with a finite friction coefficient. The oscillatory behavior of the sphere in the half-space has been analyzed by Kontomaris et al [27], which has described an analytical solution in the range of . .…”
Section: Introductionmentioning
confidence: 99%